KEWENANGAN KEPOLISIAN DALAM PROSES PENYIDIKAN - Farahwati Farahwati (Universitas 17 Agustus 1945 Samarinda, 2013)
Development of social progress quite rapidly, with the widespread phenomenon of the rule of law, human rights, globalization, democratization, decentralization, transparency and accountability are given new paradigm in seeing purpose, task, function, authority of Indonesian police republic that caused many demand and hopes of the Indonesian people about the implementation of the Indonesian National Police duties that more oriented to the communities it serves. Investigation is investigating a series of actions in terms and be regulated in law in looking for the evidence also collect the evidence, whereas he evidence could make the case easily to solve so that we could easily find the suspect of the crime. In describing subject matter, the writer try to analyse the data that the writer get, so the writer use all of the information’s, and data’s even its primary or secondary. Then try to analyse in qualitative and present in by describing the case.